REVIEW OF THE LEGAL IMPLICATIONS OF DIVORCE ON CHILD CUSTODY ARRANGEMENTS - Mau, Ellon Belwan Cornelius; Rafael, Tontji Christian (Jurnal Poros Hukum Padjadjaran, 2024)
Divorce not only entails property division but also raises significant concerns regarding child custody. Courts often intervene to determine which parent is better suited to care for the child after divorce. This research aims to explore the legal implications of divorce on child custody rights and understand the factors influencing custody decisions between fathers and mothers, both individually and jointly. Employing descriptive analysis with a normative approach, the study utilizes secondary data from primary, secondary, and tertiary legal sources. Findings suggest that divorce can result in the loss of child custody rights due to neglect of parental obligations and immoral behavior, which may have contributed to the divorce. Additionally, judges consider various factors in determining custody, including the child's welfare, emotional connection with parents, and parental responsibilities. Factors such as parental presence in the child's life, financial support, and emotional interactions with the child influence custody decisions. Therefore, it is recommended that parents maintain positive relationships with their children, prioritize family unity, and actively fulfill their duties in providing protection, affection, and proper education.